The impact of merger-related employee status on engagement, burnout and counterproductive work behaviour of employees of a South African Commercial Bank - Fourie, Paul (Stellenbosch : Stellenbosch University, 2013)
Thesis (MComm)--Stellenbosch University, 2013.